Methodological Approach to Planning and Financing the Fixed Capital Reproduction for Sustainable Development of the Fishing Industry - Terentyeva, Tatyana V.; Vasilenko, Marina E.; Titova, Natalia Y. (International Journal of Criminology and Sociology, 2022)
The article presents the results of scientific and research work on the creation of a methodological approach to the analysis of fixed capital reproduction for fishing enterprises. This study is relevant due to the fact that the fishery complex of the Russian Federation is currently called upon to provide a solution to many political and economic problems, which, in particular, include transition to an innovative type of industrial production, provision of food security, as well as maintenance of a favorable state of aquatic biological resources. Due to this industry’s high capital intensity, the issues of choosing a methodology that make it possible to rationally control the fixed capital reproduction of fishing enterprises become especially important, which is likely based on an analysis of existing methods that allow planning these processes. The advantages of the developed methodological approach include the establishment of uniform methodological principles used to determine the economic efficiency of investments, new equipment, inventions and rationalization proposals, more accurate consideration of the time factor concerning the determination of the integral economic effect (for the entire service life of labor means), as well as the factor time by bringing one-time and ongoing costs for the creation and implementation of new and necessary equipment and the results of their application to one point in time (the beginning of the accounting year). The article includes the main advantages and disadvantages of financing the reproduction processes possible ways.